Heart to heart : new poems inspired by twentieth-century American art - Jan Greenberg (China Harry N. Abrams, 2001)
What do we feel when we look at a great work of art? What does a poet feel? Heart to Heart offers an original way to approach poetry and art -- with new works by distinguished American poets, specially commissioned for this book by editor Jan Greenberg. Prompted by paintings, sculpture, prints, and photographs by American artists working in the 20th century, these poems lend a new meaning to "art appreciation" and make each page of Heart to Heart an exciting discovery.Join such poets as Jane Yolen, Nancy Willard, X. J. Kennedy, Naomi Shihab Nye, David Mura, and Angela Johnson as they reveal a personal, heartfelt response to works by Thomas Hart Benton, Romare Bearden, Jacob Lawrence, Grandma Moses, Faith Ringgold, Man Ray, Georgia O'Keeffe, and many others. Whether the poems are playful, challenging, tender, mocking, humorous, sad, or sensual, each work of art, seen through the eyes of a poet, allows readers to look at the world with new insight.
Keywords: Poetry; Poetry -- Poetry